1984
DOI: 10.1016/0014-5793(84)80773-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the functional molecular size of vasopressin isoreceptors

Abstract: The molecular size of vasopressin receptors in the intact membrane-bound state was determined by radiation inactivation (target size analysis). For the V1 receptor in rat liver a molecular size of (76 +/- 8) kDa was determined. For the V2 receptor in rat kidney and bovine kidney molecular sizes of (95 +/- 4) and (108 +/- 11) kDa were found. Statistical analysis gave evidence for size differences between rat liver and rat kidney receptors or differences between rat liver and bovine kidney receptors, but not bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Al though these studies report receptor molecular weights ranging from 60 to 100 kD, most are consistent with those we have found [23,24,[27][28][29]. For instance, Knigge et al [24], using quite similar techniques, reported molecular weights of 55 and 62 kD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Al though these studies report receptor molecular weights ranging from 60 to 100 kD, most are consistent with those we have found [23,24,[27][28][29]. For instance, Knigge et al [24], using quite similar techniques, reported molecular weights of 55 and 62 kD.…”
Section: Discussionsupporting
confidence: 88%
“…In previous experi ments, Knigge et al [22] have shown that vasopressin competes with a vasopressin anti-idiotype antibody for receptors on the paraventricular and supraoptic nuclei of the hypothalamus. The same investigators [22,29] also have reported that PVA (the 5'-3' complement of AVP) and a vasopressin-binding protein prepared from rat brain membranes were capable of blocking the staining of AVP receptors by vasopressin anti-idiotype an tibody. This evidence suggests that the receptor/vasopressinbinding protein and PVA have similar binding site structures, as they both bind to the anti-idiotypic antibody.…”
Section: Discussionmentioning
confidence: 96%
“…Membrane-bound tritiated hormone was separated from free hormone by rapid filtration over cellulose acetate filters (0.22 pm). The filters were washed twice with the filtration medium and counted as described [15]. Specific binding was obtained by the difference between 3H-labelled ligand binding in the absence and presence of a 100-fold excess of unlabelled hormone.…”
Section: Preparation Of Membrane Fractionsmentioning
confidence: 99%
“…Vasopressin induces the pressor and antidiuretic response through activation of two separate receptors, the V1-and V2-receptor respectively (Michell et al, 1979). The receptors are coupled to different intracellular second messengers and differ in their molecular size Crause et al, 1984). For example, Vl-receptor activationinhepatocytesisrelatedtoinositolphospholipid hydrolysis and intracellular Ca2, mobilization, whereas V2-receptor activation in renal tubular cells leads to an increase of cyclic AMP (Kirk et al, 1977(Kirk et al, , 1979(Kirk et al, , 1981Michell et al, 1981;Thomas et al, 1984;Charest et al, 1985;Butlen et al, 1978).…”
Section: Introductionmentioning
confidence: 99%